The Effect of Electronic Word of Mouth, Brand Image, and Brand Trust on Consumer Purchase Decision on Camille Organic Beauty Face Mask - Alifda Dizzania Oktaviani; Dicky Wisnu Usdek Riyanto; Iqbal Ramadhani Fuadiputra (Universitas Muhammadiyah Malang, 2022)
This study aims to determine the effect of electronic word of mouth, brand image, and brand trust on purchasing decisions of consumers of organic face mask Camille beauty in the city of Malang. This type of research is quantitative research. The sampling technique uses purposive sampling. The sample in this study was 166 respondents. The data collection technique used a questionnaire in the form of a google form which was distributed online through social media and analyzed using SPSS version 25. The results showed that electronic word of Mouth had a positive and significant effect on buying decisions. Brand Image has a significant effect on purchasing decisions. Brand Trust has a positive and significant effect on purchasing decisions. electronic word of mouth, brand image, and brand trust simultaneously on purchasing decisions, the three independent variables have the same positive and significant effect on purchasing decisions.